Artificial intelligence-enabled atrial fibrillation detection using smartwatches: current status and future perspectives - Papalamprakopoulou, Zoi; Stavropoulos, Dimitrios; Moustakidis, Serafeim; Avgerinos, Dimitrios; Efremidis, Michael; Kampaktsis, Polydoros N. (Frontiers in Cardiovascular Medicine, 2024)
This mini review is intended for the Research Topic "Artificial Intelligence for Arrhythmia Detection and Prediction". We specifically focus on detection of atrial fibrillation using smartwatches. The review first summarizes the techniques for atrial fibrillation detection and then describes the technical aspects of artificial intelligence algorithms that aim to improve the diagnostic accuracy of smart watches. We then describe the clinical implications of this minimally invasive detection methodology, and specifically which populations may benefit from screening with artificial intelligence-enabled smartwatch detection.